Respuesta :
Answer:
c
Step-by-step explanation:
Solution by substitution method
x+2y=12
and -x=-y-6
∴-x+y=-6
x-y=6
Suppose,
x+2y=12→(1)
and x-y=6→(2)
Taking equation (1), we have
x+2y=12
⇒x=-2y+12→(3)
Putting x=-2y+12 in equation (2), we get
x-y=6
(-2y+12)-y=6
⇒-2y+12-y=6
⇒-3y+12=6
⇒-3y=6-12
⇒-3y=-6
⇒y=2→(4)
Now, Putting y=2 in equation (3), we get
x=-2y+12
⇒x=-2(2)+12
⇒x=-4+12
⇒x=8
∴x=8 and y=2
9514 1404 393
Answer:
c. (8, 2)
Step-by-step explanation:
Multiplying the second equation by -1 gives an expression for x that can be substituted into the first equation.
x = y +6
(y +6) +2y = 12
3y = 6 . . . . . . . subtract 6
y = 2 . . . . . . . . eliminates all choices except C
Using the expression for x, we can find the complete solution:
x = y +6 = 2 +6 = 8
(x, y) = (8, 2) . . . . matches choice C